(untitled) - Lednicer, Daniel (New York, 1990)
Volume 4 of this series is addressed primarily at practitioners in the field who seek a quick overview of the synthetic routes which have been used to access specific classes of therapeutic agents. This volume covers the chemistry of those compounds which have been granted a United States Adopted Name (USAN) in the five years between 1983 and 1987. Many examples of actual applications of chemistry are provided by this book, which presumes a good working knowledge of chemical synthesis and at least a passing acquaintance with biology and pharmacology.
Keywords: Pharmaceutical chemistry,Organic compounds,Hóa dược phẩm,Hợp chất hữu cơ; Synthesis,Sự tổng hợp